2014
DOI: 10.6002/ect.2013.0110
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Objectives: Cardiovascular disease is a common cause of morbidity and mortality in patients with chronic kidney failure, before and after a kidney transplant. Oxidation of lipoproteins that contain apolipoprotein B may contribute to the initiation of atherosclerosis. Paraoxonase may prevent cardiovascular disease. We compared the effects of different calcineurin inhibitors on risk factors for cardiovascular disease in kidney transplant recipients. Materials and Methods: In 16 kidney transplant recipients, trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…It has been shown that erythropoietin β and iron treatment has a beneficial effect on the levels of antibodies against oxidized LDL and on serum PON1 activity in pre dialysis patients with chronic renal disease and anemia [ 76 ]. Immunosuppressive drugs and especially the calcineurin inhibitor tacrolimus, may be more effective than cyclosporine as regards paraoxonase and arylesterase activities in CKD patients before and after 12 months of kidney transplant (KT) [ 77 ]. The modulating effect of hydroxymethyl glutaryl-coenzyme A (HMG-CoA) inhibitors (statins) on PON1 activity in type 2 diabetic nephropathy (T2DN) patients was investigated as well [ 68–70 ].…”
Section: Main Factors Influencing Pon1 Activity In Chronic Kidney Dis...mentioning
confidence: 99%
“…It has been shown that erythropoietin β and iron treatment has a beneficial effect on the levels of antibodies against oxidized LDL and on serum PON1 activity in pre dialysis patients with chronic renal disease and anemia [ 76 ]. Immunosuppressive drugs and especially the calcineurin inhibitor tacrolimus, may be more effective than cyclosporine as regards paraoxonase and arylesterase activities in CKD patients before and after 12 months of kidney transplant (KT) [ 77 ]. The modulating effect of hydroxymethyl glutaryl-coenzyme A (HMG-CoA) inhibitors (statins) on PON1 activity in type 2 diabetic nephropathy (T2DN) patients was investigated as well [ 68–70 ].…”
Section: Main Factors Influencing Pon1 Activity In Chronic Kidney Dis...mentioning
confidence: 99%
“…This gradient in PON1 enzymatic activity is consistent with the gradient of kidney function. However, all studies have been cross-sectional in nature, with the exception of a study comparing change in arylesterase at 1, 6 and 12 months post-transplant ( 10 ). There has been no prospective determination of change in PON1 mass and activity with prospective restoration of kidney function through KT.…”
Section: Introductionmentioning
confidence: 99%